Utilization of maternal nutrition services during antenatal care and its association with nutrition practices in Bangladesh, Burkina Faso, Ethiopia, and India - Kachwaha, Shivani; Kim, Sunny S.; Mai, Lan T.; Sanghvi, Tina; Mahmud, Zeba; Zafimanjaka, Maurice G.; Walissa, Tamirat; Ghosh, Sebanti; Nguyen, Phuong Hong (2024)
Objectives: Adequate coverage of antenatal care (ANC) and its related services are essential for maternal and newborn health and nutrition. Interventions to strengthen health systems in the delivery of nutrition interventions during ANC were implemented in Bangladesh (BD), Burkina Faso (BF), Ethiopia (ET), and India (IN). This study examined the coverage and equity of ANC services and the association between service utilization and maternal nutrition practices.